Application of an Mn-MOF as a highly efficient catalyst for sunlight-driven hydrogen generation. (2nd November 2018) - Luo, Mingjin; Wang, Youliang; Huang, Tingbo; Su, Ting; Fu, Donghui; Yue, Santang; Zeng, Heping
ABSTRACT: Microscale crystals of a 2D layered Mn-MOF [Mn2 (TylP)4 ] n (TylP=5-(1, 2, 4-triazol-1-yl)isophthalic) with a thiolate-bridged binuclear Mn(II) node similar to the active site of the [MnAu]-hydrogenase were prepared. This material shows high catalytic activity for visible-light-driven hydrogen production under the illumination of white LED or direct sunlight. The turn-over frequency of the catalyst can reach up to 6 h −1 . In this study, the heterogeneous nature and recyclability of the catalyst, as well as the factors that affect the catalytic activity have been investigated and described. Moreover, the photocatalytic mechanism for the hydrogen generation of [Mn2 (TylP)4 ] n has also been proposed, based on fluorescence spectra and cyclic voltammetry.